WORKSHOP KEWIRAUSAHAAN “PENGEMBANGAN INDUSTRI KREATIF DI KALANGAN MAHASISWA MENUJU GENERASI BERDAYA SAING WIRAUSAHA” UNTUK MAHASISWA PROGRAM STUDI GEOGRAFI FISIP UNIVERSITAS LAMBUNG MANGKURAT - Sari, Erini Junita; Hanifah, Hanifah (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
This community service was held at the Lecture Theatre of Lambung Mangkurat University for students of the Geography study program FISIP Lambung Mangkurat University, Banjarmasin City. This community service aims to instill an understanding of the importance of entrepreneurship and creative economy among students of the Geography Study Program, FISIP, Lambung Mangkurat University. This community service is expected to reduce the risk of declining growth rates of young entrepreneurs in the midst of 17 creative economy sectors and is expected to help improve the welfare of students in the city of Banjarmasin. The method used in this community service is socialization related to Entrepreneurship, Creative Economy, and Business Legality. The result of this community service is an increase in participants' understanding of Entrepreneurship, Creative Economy, and Business Legality. Participants managed to understand what are the types of creative economy and business legality, as well as better understand the importance of entrepreneurship.